(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Blockchain is a decentralized technology. When it comes to resolving business issues, it wields considerable power. Every transaction on the blockchain is encrypted, and each transaction is linked to a previous transaction or record. Blockchain transactions are validated by algorithms running on nodes. A single entity cannot start a transaction. Eventually, blockchain provides transparency by allowing any participant to view transactions at any moment. Smart contracts provide secure transactions, minimizing the risk of third-party interruptions. Ethereum is a decentralized platform based on smart contracts. It enables developers to create markets that transfer money according to the instructions given years ago. Blockchain is distinguished by two key characteristics: immutability and decentralization. Deals are completed faster; Transactions and authentication are completed in a matter of seconds, and much more.